Analysis of a Novel Magnetic-Hydrodynamic Double Levitated Motor for an Implantable Axial Flow Blood Pump - Liang Wang; Xiaoyan Tang; Zhong Yun; Chuang Xiang (Shock and Vibration)
This paper presents a novel design for a bearingless axial flow blood pump based on the magnetic-hydrodynamic double levitated concept. In the axial direction, the magnetic levitation system consisted of two pairs of permanent magnet rings offsets the force of fluid. The hydrodynamic shell mounted on the impeller rotor is designed for generating dynamic pressure, which can balance the radial force like gravity when the blood pump is working. Because of the unsteady force and torque acting on the rotor and the passive suspension, the position of the rotor is not steady. The suspension force, stiffness, and torque of the rotor are calculated by the theoretical method and finite element method. Then, the dynamics of the rotor are analyzed. Arrangements of Hall-effect sensors with the corresponding data acquisition system which can measure the axial displacement of the rotor are explained. The sensorless drive control system for the blood pump is described too. With a prototype pump, an external circulation experiment system is built and then the axial and radial displacements of the rotor are measured by using Hall-effect sensors and the laser vibrometer under different working conditions.